What do we know about Cassis tuberosa (Mollusca: Cassidae), a heavily exploited marine gastropod? - Dias, Thelma Lúcia Pereira; Mota, Ellori Laíse Silva; Duarte, Rafaela Cristina de Souza; Alves, Rômulo Romeu da Nóbrega (Ethnobiology and Conservation, 2017)
Cassis tuberosa is a key species in reefs and sandy beaches, where it plays an essential role as a predator of echinoderms (sea urchins and sand dollars). Due to the beauty of its shell, it is one of the most exploited species for trade as marine souvenirs throughout its distribution in the Western Atlantic. Despite its ecological importance, there is little available information about population and biological data or the impacts of its removal from its natural habitats. Considering the economic and ecological importance of this species, this study provides a short review of existing studies and highlights research and conservation needs for this highly exploited marine gastropod.